(untitled) (Universal International Scientific Journal, 2026)
This article will examine the views and wise advice of our great ancestors, great thinkers and scientists Abu Ali ibn Sina, Abu Nasr Farobi, Abu Rayhan Beruni, and Alisher Navoi on morality, education, and upbringing, and will highlight the importance of education in the upbringing of young people, what to pay special attention to in raising children, and the important role of education in shaping a child’s personality, as well as the ways to implement it and the issues of raising children properly.